Surgical management of fracture shaft tibia with closed interlocking intramedullary nailing – A clinical study - Rao, N V Narasimha; K, Dr. Ravikanth; Rama Reddy, Tetali Venkata; Chandra, T Jaya (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Introduction: The tibia being the most commonly fractured long bone. A study was conducted to analyze the efficacy of closed intramedullary nailing tibial shaft fractures. Materials and methods: Study was conducted in the Department of orthopedics. Individuals with closed tibial diaphyseal fractures of >18 years, open diaphyseal fractures of tibia type I, type II were included. Open diaphyseal fractures of tibia Type III A, B, C, tibial fractures with intraarticular extensions and medically ill were excluded. Under spinal anesthesia, intramedullary locking was done as per the protocol. Results: During the study period, 50 fractures were included. the male-female ratio was 5.25. The youngest patient was 19 years and the oldest patient was 67 years. 60% of the participants had right tibial fractures and 40% with left. Thirty-nine (78%) participants simple and 22% (11) had type I and type 11 compound fractures. The majority of fractures (58%; 29) were united within 18-20 weeks. The average healing time was 19 weeks. Conclusion: In this study 16.9 weeks was the average healing time and 76% patients showed excellent outcome.